Scotland’s Catholics, the Papal States and the pope’s temporal sovereignty, 1860–1870 - Tierney, Darren (The Innes review, 2025)
Scotland’s role in defending Pope Pius IX’s temporal sovereignty during the final decade of the Papal States has received little scholarly attention. Yet Scottish Catholics played a discernible part through expressions of sympathy, fundraising efforts, and ultimately military service, most notably the 120 men from Glasgow who joined the papal army in 1867. Drawing on archival sources and recent transnational scholarship, this article situates Scotland’s contribution within wider European Catholic responses, shaped by ultramontanism and by strengthening ties between Scotland and Rome. It also looks at the social backgrounds and motivations of the volunteers, the controversies surrounding their service, and the tensions between Irish and Scottish Catholic identities. Although the primary evidence is limited, Scotland’s involvement in these events tells us about a broader Catholic solidarity and international outlook, inviting a fuller consideration of Scottish Catholic history in global religious and political contexts.